Penataan Ulang Gudang Penyimpanan Kain Jadi Untuk Mengatasi Penumpukan di Gudang Kain Jadi PT. SIPATEX - Chandrahadinata, Dody; Tapajani, Dedi Sa'dudin; Sundari, Ayu (Institut Teknologi Garut, 2025)
Rapid development in the industry, driven by improvements technology, has complicated the challenges faced. Within sectors manufacturing, difficulties often arise in arranging the layout finished product warehouse. Based on observations at PT Sipatex, the arrangement of finished products in the warehouse is still not well organized, which results in inefficiency. The time required for picking up products in different areas of the warehouse takes longer, and This also makes it difficult for workers to inspect goods which will be sent to customers. The main challenge is currently facing PT Sipatex is a lack of internal organization product arrangement, which can slow down the delivery process and causing some aisles not to match the size of the equipment material handling, making it difficult for forklift operators in pick up finished products at the warehouse. This research aims to provide recommendations for improving product layout in the fabric warehouse so with a focus on reorganizing material handling in order to deal with buildup of finished fabric more effectively, so can reduce product buildup in warehouses. The method used in warehouse management is an approach shared storage, where products with delivery frequency the highest and the ones that move frequently are placed closer to the entrance to minimize handling movement distance material. This shared storage approach successfully reduces average material handling mileage per week of 380.5 meters to 292.7 meters per week